2019
DOI: 10.1002/jcb.28405
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells improve platelet counts in mice with immune thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is a common autoimmune bleeding disorder. The breakdown of immune tolerance (regulatory T [Treg] cells and suppressor cytokines) plays an important role in ITP pathophysiology, especially in refractory ITP. Bone marrow-derived mesenchymal stem cells (BM-MSCs) show immunomodulatory properties and have been extensively utilized for autoimmune diseases. However, it has not been fully elucidated how BM-MSCs affect ITP. In this study, we explore the therapeutic mechanism of BM-MSCs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Treatments with MSCs + TAT NP and MSCs + TAT PTX NP resulted in about 30% to 60% increase in platelet count (Table 2). Previous studies have shown that MSCs can increase platelet count through induction of interlukein-10 (IL-10) and TGF-β [36]. None of the other hematological parameters were affected by the treatments (Table 2, Table S1).…”
Section: Resultsmentioning
confidence: 92%
“…Treatments with MSCs + TAT NP and MSCs + TAT PTX NP resulted in about 30% to 60% increase in platelet count (Table 2). Previous studies have shown that MSCs can increase platelet count through induction of interlukein-10 (IL-10) and TGF-β [36]. None of the other hematological parameters were affected by the treatments (Table 2, Table S1).…”
Section: Resultsmentioning
confidence: 92%
“…ITP-MSCs cannot proliferate routinely and are defective in immunomodulation. Exogenous BM-MSCs have been shown to reverse this defect of proliferation and immunomodulation in both in vitro cytological experiments and in vivo animal experiments [32,33]. Substantial differences exist between BM-MSCs and BM-MSCs in ITP (ITP-MSCs) in terms of their appearance, proliferation, apoptosis, senescence, and differentiation (Table 2) [14,34,35].…”
Section: Bm-mscs In Itpmentioning
confidence: 99%
“…MSCs have been demonstrated to be beneficial for ITP mice. 15 To better understand the role of miR-98-5p in MSCs during ITP, we established an active ITP model and injected ITP mice with miR-98-5pmodified MSCs to observe the resultant therapeutic effects. One week after transferring immunized splenocytes, platelet counts significantly decreased in ITP mice (Figure 5A), and there was obvious bleeding in subcutaneous tissues, abdomen, lungs, and intestines.…”
Section: Mir-98-5p Overexpression Impairs the Treatment Effects Of Mscs In Itp Micementioning
confidence: 99%
“…11 Based on the ability to modulate immune responses, MSCs have been used in the treatment of various inflammatory diseases, such as steroid-resistant acute graft-versus-host disease, cardiovascular disease, and autoimmune disorders. [12][13][14] In particular, MSCs have been reported to be efficacious in improving platelet levels in ITP mice, 15,16 and the intravenous infusion of umbilical cord-derived MSCs seems to be effective in refractory ITP patients. 17 Given the promising therapeutic effects of MSCs in ITP and the key roles of MSCs during ITP development and progression, it is necessary to investigate the precise molecular signals that lead to MSC dysfunction in ITP.…”
Section: Introductionmentioning
confidence: 99%